REKONSTRUKSI PARADIGMA FITRAH MANUSIA SEBAGAI FONDASI EPISTEMIK DAN PEDAGOGIK DALAM MITIGASI DEKADENSI MORAL DI ERA DISRUPSI DIGITAL - Abdul Rasyid; Habib Anwar Al-Anshari (STKIP Subang, 2026)
This paper aims to explore in depth the concept of human nature from an Islamic and psychological perspective and its relevance as a mitigation instrument against the phenomenon of moral degradation in the digital era. The main problem identified is the occurrence of psychospiritual disequilibrium in the younger generation due to unfiltered exposure to information technology, which causes alienation from the sacred nature of humanity. The urgency of this task lies in the urgent need for an educational framework capable of maintaining the moral integrity of students amidst the currents of modern materialism and secularism. The methodology applied is a literature study (library research) using a qualitative-descriptive approach, synthesizing classical texts and contemporary findings. The results indicate that fitrah is a dynamic, innate potential encompassing monotheism, intellectual, and moral dimensions that requires a conducive environment for its actualization. These findings confirm that the success of character education depends heavily on aligning learning methods with natural human development patterns through a holistic and integrative approach.